The Relationship of Screen Tme with sleep Patterns in Toddler Children at Posyandu Mlaten Village - Peni, Tri; Laili, Siti Indatul; Pratiwi, Chaterina Janes; Kamelia, Arina (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Screen time in front of an electronic screen for a long time causes disturbances in children's sleep patterns, so that children will have difficulty concentrating, become irritable and appear tired. The aim of the research was to determine the relationship between screen time and sleep patterns in toddler children at the Posyandu in Mlaten Village. The research design used cross sectional. The population in this study were all mothers who had children aged 12-36 months at the Mlaten Village Posyandu, totaling 61 respondents. The sampling technique uses purposive Sampling. The research instrument uses sleep disturbance scale for children (SDSC). Data analysis using spearman rho. The research results showed that the majority of respondents who had high screen time activities (>120) per day experienced disturbed sleep patterns (95%). Spearman Rho test results show p value of 0.000. There is a relationship between screen time and sleep patterns in children. Excessive exposure to electronic screens with screen lighting that is too bright suppresses the secretion of melatonin, which regulates the sleep-wake cycle by influencing sleep phase delays. This causes disturbances in the quantity and quality of children's sleep.